Generation Y's perception of servant leadership and job satisfaction - Hurriyet Bilge; Florina Oana Virlanuta; Deniz Zungun; Nicoleta Bărbuţă-Mişu; Pinar Comuk; Emine Turkan Ayvaz Guven (Economies, 2021)
Generation Y wants to know the reason for everything in their lives, they are curious and most importantly, their characteristic of questioning everything makes them stand out. At the same time, it is hard to influence their characteristic features such as their lack of social skills, little respect for authority, and low level of commitment to their employers when Generation X management tactics are used. The purpose of this study is to better understand Generation Y, to examine their relations with servant leadership practices, and to determine what effects they have on businesses. The field study was made at an established organized industrial zone (OIZ) dating back to 1963. This OIZ is built on an area bigger than 10 million m2 and is divided into 5 subzones. It is currently home to 53,500 employees, has a gross foreign trade volume of 7,200,000,000 and is located in the western Aegean Region of Turkey. The data for the study was collected from 248 participants and scales tested for validity and reliability in Turkish. A model was developed using the data and then it was tested using the confirmatory factor analysis method. The study used Structural Equation Model (SEM) to define the causal relationships between latent variables with a model in the analysis of the data and test its compliance. The result of the analysis reveals that dimensions of accountability and forgiveness from servant leadership practices have a statistically significant effect on personal success, whereas empowerment, accountability, and personal success dimensions have statistically significant effects on job satisfaction. Modesty dimension does not have a significant effect on the personal success and job satisfaction and the dimensions of accountability and forgiveness do not have a significant effect on job satisfaction. In addition, empowerment dimension does not have a meaningful effect on personal success. There is need for more studies to support the accuracy of the result for modesty dimension, since it seems like there is no effect on personal success and job satisfaction. This is a pioneer study since it is an empirical one looking at the application of the servant leadership theory on Generation Y employees
Keywords: 330; Generation Y; servant leadership; job satisfaction; personal success; Structural Equation Models (SEM)